A time-dependent perturbation solution from a steady state for Marangoni problem. Issue 9 (4th July 2018) - Wang, Huichao; Wang, Quan; Liu, Ruikuan
Abstract: In this article, based on the T -weakly continuous theory, we prove the existence of global weak solution of the 2D incompressible Marangoni problem, which is modelled by the Boussinesq equations omitting effect of buoyancy. Moreover, we show that such weak solution is unique, and which is a time-dependent perturbation solution from a steady state.